O homem homossexual e a fenomenologia do seu envelhecer - ROCHA, Jefther Felipe Lima (2023)
The study aimed to present an intentional analysis of the experiences of aging gay men. There was a lack of scientific material focusing on the experiences of gay men regarding aging, from a phenomenological perspective, which, therefore, justified the original nature of this investigation. The following guiding question guided the research: how do cisgender homosexual men experience their own aging? To answer this question, the general objective of the research was: to understand the experiences of cisgender homosexual men regarding their aging. As specific objectives, identify the invariant structures (essences) of the subjects' experiences; systematize listening to experiences by carrying out their transcendental reduction and revealing characteristics that the aging of cisgender homosexuals can assume. This qualitative non-experimental empirical research was carried out from the epistemological, theoretical and methodological perspective of Edmund Husserl's Phenomenology (1859-1938). To access the participants' written reports, a digital form via Google Forms was used. The research included 26 participants from 7 Brazilian states. From the application of the phenomenological method, it was possible to understand that the participants described aging as a multifaceted process that encompasses changes in physical, psychological and social dimensions. Their insights highlighted specific challenges related to acceptance, appreciation, concerns about finitude and decay. Furthermore, the research revealed the persistence of stigma and discrimination faced by this population as they age. The study highlighted the importance of providing emotional support, psychotherapeutic interventions and education sensitive to the specific needs of these individuals, thus promoting well-being and dignity throughout aging.